IMPLIKASI PERAN DESTINATION MANAGEMENT ORGANIZATION (DMO) – DESTINATION GOVERNANCE (DG) DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN - Mahardhika Berliandaldo; Angga Wijaya Holman Fasa; Dini Andriani (JURNAL KEPARIWISATAAN, 2022)
This study analyses the implications of Destination Management Organization (DMO) – Destination Governance (DG) on sustainable tourism development in Indonesia. Desk study is carried out using secondary data and VRIO analysis was employed. We found that the success of DMO development cannot be separated from the transformation of DMO development which includes the stage of strengthening the collective awareness movement of stakeholders; the destination management development stage; the business development stage; and the stage of strengthening and structuring the destination management organization. The development of DMOs in various countries is carried out on a regional and national scale by developing tourism boards that aim to develop tourism, technology and information as well as the promotion of tourist destinations. The implications of competitiveness through capability resources in DMO-DG, obtained 4 (four) Sustained Competitive Advantages, including tourism ecosystem, quality of service and travel experience, human resource development, and community management.